Early life adversity and appetite hormones: The effects of smoking status, nicotine withdrawal, and relapse on ghrelin and peptide YY during smoking cessation. (July 2021) - al'Absi, Mustafa; DeAngelis, Briana; Nakajima, Motohiro; Hatsukami, Dorothy; Allen, Sharon
Highlights: Early life adversity was positively associated with elevated ghrelin in nonsmokers. Greater peptide YY was associated with reduced urges to smoke during withdrawal . Among those reporting no early life adversity, relapsers had greater ghrelin than nonsmokers during withdrawal. Abstract: There is evidence suggesting that ghrelin and peptide YY (PYY) modulate stress responses and the rewarding effects of drugs, although no research has examined the impact of exposure to early life stress on these hormones in smokers nor during smoking cessation. This study examined the relationships between early life adversity (ELA) and circulating ghrelin and PYY during ad libitum smoking and early withdrawal in tobacco smokers (N = 98) who were interested in cessation. We also included a comparison group of nonsmokers (N = 36). We prospectively compared levels of hormones between smokers who were successful in quitting within a 2-week period, smokers who relapsed during that period, and nonsmokers. Results showed that ELA was positively associated with elevated ghrelin in nonsmokers . Among those reporting no ELA, successful quitters had higher ghrelin levels than nonsmokers during ad libitum smoking, while relapsers had higher ghrelin levels than nonsmokers during withdrawal. In addition, having no ELA was associated with a decline in ghrelin from the ad libitum to abstinence sessions in successful quitters; this withdrawal-related decline was not found in relapsers. Although effects of ELA, smoking group, and time on PYY were not significant, greater PYY was associated with reduced urges to smoke during withdrawal . These findings suggest the importance of considering changes in appetite-related hormones in individuals who are dependent on tobacco. This research provides additional indications for effects of ELA on appetite-stimulating hormones.